The association between ambient temperature and elite racewalking performance in the olympics and world championships - Zhang, X.; Cui, D.; Jiang, Z.; Yang, W. (Frontiers in Sports and Active Living, 2025)
Introduction: Global warming has become one of the major challenges in athletics, with evidence suggesting that racewalking is susceptible to high ambient temperature, though the magnitude of this relationship remains uncertain. This study aimed to investigate the relationship between weather conditions and racewalking performance in major international events, and examine differences across sex, performance levels, and race segments.